Immobilization of 5‐Fluorouridine on Chitosan. Issue 10 (16th October 2013) - Malecki, Edith; Viere, Rebecca; Rosemeyer, Helmut
Abstract The 2′, 3′‐O‐levulinic acid derivative 2b of the cancerostatic 5‐fluorouridine as well as its N(3)‐farnesylated nucleolipid 2d were synthesized and coupled to H2O‐soluble chitosanes of different molecular weight and at various pH values (3.5–5.5) leading to 6 and 7. In addition, the coumarine fluorophore ATTO‐488 N(9)‐butanoate was bound to the biopolymer by a sequential‐coupling technique to afford 9 and 10. Moreover, chitosan foils were prepared, to which 2b was coupled. Their degradation by chitosanase (from Streptomyces sp. N174) was studied UV‐spectrophotometrically in a Franz diffusion cell.